Outcome of Placenta Percreta Management by Planned Peripartum Hysterectomy in a Tertiary Level Hospital - Zesmin, Fahmida; Zeba, Dilruba; Biswas, Rajib; Fatema, Kaneez; Alam, Samiya; Khanam, Shafeya (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
The incidence of placenta accreta spectrum is gradually increasing due to increased rate of caesarean sections (CS). Due to torrential haemorrhage, placenta percreta is one of the main reasons for emergency peripartum hysterectomies and mostly results in subsequent maternal mortalities and morbidities. In such cases, caesarean hysterectomy leaving the placenta in situ without any separation of placenta is preferred. We observed the outcome of such patients managed with planned caesarean hysterectomy. This cross-sectional observational study was conducted at the Department of Obstetrics, Faridpur Medical College Hospital, Bangladesh. A total of 14 patients who underwent planned caesarean hysterectomy due to placenta percreta were studied. We performed delivery of the baby through upper segment transverse incision without placental separation. The umbilical cord was ligated leaving the placenta in the uterine cavity and cut margins of the uterus was closed with few interrupted sutures and then hysterectomy was performed. Among 14 cases, the mean age was 30 years, mean gestational age at the time of delivery was 36 weeks, and all had a history of one or more CS. Before operation, mean Hb% was 8.9 g/dl. A mean of 1.5 units pre-operative and 1.2 units post-operative blood transfusions was needed. Post-operative mean Hb% was 10.5 gm/dl. Half of the women were discharged on their 3rd post-operative day. None of them had serious pre- and post-operative complications. In light of our findings, we recommend managing placenta percreta by planned caesarean hysterectomy with the placenta left in situ to minimise blood loss and subsequent maternal mortality and morbidity. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(2):80-84